Implementation Of Tri Hita Karana Teachings In Subak Activities In Bali - Ni Gusti Ayu Agung Nerawati (Jayapangus Press, 2020)
Revealing the life of traditional farmers in modern times nowadays seems like reminiscing about a past life. Advances in technology and communication led to shifts in several aspects of people's lives, including Balinese people who mostly Hinduism. This shift does not only occur at the social level, such as daily life but also on the public mindset which leads to a mindset that prioritizes all material interests. Even though, there are still many Balinese people, especially those living in rural areas, who still show mindset and lifestyle like those found in the past and shown in their daily lives today. This is still strong in the traditional farmers’ life.